A 3D Network of Nanochannels for Possible Ion and Molecule Transit in Mineralizing Bone and Cartilage. Issue 8 (28th April 2022) - Tang, Tengteng; Landis, William; Raguin, Emeline; Werner, Peter; Bertinetti, Luca; Dean, Mason; Wagermaier, Wolfgang; Fratzl, Peter
Abstract : During crucial growth stages of vertebrate long bones, calcified cartilage beneath the growth plate is anchored to bone by a third mineralized component, the cement line. Proper skeletal development is contingent on the interplay of these three constituents, yet their mineralization processes and structural interactions are incompletely understood, in part from limited knowledge of their meso‐ and nanoscale features. Herein, focused ion beam‐scanning electron microscopy (FIB‐SEM) with serial surface imaging is applied to examine the cartilage–bone interface of mouse femoral heads at an unprecedented scale: FIB‐SEM provides 3D, nanometer resolution of structural details for volumes encompassing metaphyseal calcified cartilage, bone, and the intervening cement line. A novel and complex structural network is revealed, comprising densely packed nanochannels smaller than bone canaliculi (≈10–50 nm diameter) within the calcified cartilage and bone extracellular matrices, but absent in the cement line. A structural correlation is demonstrated between the nanochannels and ellipsoidal mineral domains, which appear to coalesce during mineralization in a process analogous to powder sintering in metallurgy. A mineralization process is proposed, supported by energy‐dispersive X‐Ray spectroscopy of nanochannel contents, in which these unreported structures offer ion and molecule conduits to access the extracellular matrices of calcified cartilage and bone. Abstract : This study reveals a previously unknown and extensive nanochannel system that penetrates both calcified cartilage and bone at the cartilage–bone interface of the mouse femoral head. Such nanochannels are associated with mineral domains and contain organic elements, features suggesting a ubiquitous mineralization process where the nanochannels facilitate progressive growth of the mineral ellipsoids through transport of ions and small molecules.